A Non-stationary Gale Economy with Limit Technology, Multilane Turnpike and General Form of Optimality Criterion - Panek, Emil (Central and Eastern European Economic Review, 2019)
The paper refers to my previous works: “«Słaby» efekt magistrali w niestacjonarnej gospodarce Gale’a z graniczną technologią i wielopasmową magistralą produkcyjną” (in: Matematyka i informatyka na usługach ekonomii, D. Appenzeller (ed.), 2017) and “Niestacjonarna gospodarka Gale’a z graniczną technologią i wielopasmową magistralą produkcyjną. «Słaby», «silny» i «bardzo silny» efekt  magistrali” (Przegląd Statystyczny 2018, 65(4)), and contains proofs of weak and very strong turnpike theorems in a non-stationary Gale economy with limit technology and multilane turnpike. In contrast to the above-mentioned papers, the growth criterion is the maximization of discounted additive production utility over production in all periods of the economy’s time horizon T.